The Impact of RCEP Agreement on China-ASEAN Agricultural Trade: An Analysis Based on GTAP Model - Hu, Guante; Li, Dongsheng (International Journal of Global Economics and Management, 2024)
Agricultural trade between China and ASEAN is an important part of bilateral trade and plays an important role in promoting agricultural development and advancing rural revitalization. The trade ties between China and RCEP member states, especially with ASEAN countries, have increased with the implementation of the RCEP. Although the development of agricultural trade between China and ASEAN has already reached a considerable scale. As an important partner of China in agricultural trade, studying the impact of the RCEP agreement on China's agricultural trade with ASEAN has practical significance in strengthening agricultural trade cooperation between China and ASEAN countries and fully utilizing the policy benefits of the RCEP agreement to release the potential of agricultural trade.